Pernikahan Anak Usia Dini dan Konstruksi Identitas Gender: Analisis Teori Peter L. Berger (Studi di Desa Pandansari Poncokusumo Kabupaten Malang) - Agustin, Dewien Nabielah; Nurharini, Firdausi; Hasan, Laili Mas Ulliyah (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2023)
Early marriage often becomes a prevalent culture in rural areas. This is primarily attributed to a lack of knowledge and the inability to meet the family's livelihood needs. The underlying basis for early marriages is how the community supports their underage children to engage in matrimony. An exploration of the meaning of early marriage and the family's role in early marriages is a novel aspect to present. This research aims to describe how early marriages are interpreted on both a national and international scale. Unlike other studies that tend to focus on external aspects of marriage, this research views marriage within the context of gender identity construction. The data collection method employed in this research is the interpretative understanding constructivist approach with a phenomenological framework. It adopts an approach of interpretative understanding analysis. The results indicate three key factors related to early marriages in rural areas: (1) Arranged marriages are a supportive factor for early marriages, (2) Social support, particularly the role of the family head, plays a crucial role in early marriages due to the prevailing tradition of arranged marriages within the community, and (3) The education levels within the community and among adolescents remain insufficient in terms of understanding the consequences of early marriages. The conclusion drawn from this research is that the socio-cultural norms present in the community can be used as one of the approaches to reduce the prevalence of early marriages. Formal education emerges as a primary area that has been overlooked by both adolescents and parents, thus aiding in reducing early marriages in rural areas.